Knowledge of nurses about care of patients on hemodialysis in intensive care units (Research, Society and Development, 2022)
Objectives: Stablish the nurse’s level of knowledge regarding nursing care for critical patients under hemodialysis. Method: Quantitative, descriptive and exploratory study carried out among intensive care nurses in a public tertiary hospital, using an instrument with sociodemographic and theoretical-practical issues. Results: 57 nurses participated with predominancy of female nurses (91.2%) and assistance functions (50.9%). The nurses were on average age of 32.9 years old, graduated for 6.2 years and have been working at their current positions for 1.9 years. There was a deficiency of knowledge regarding the evaluation of urinary output and kidney function. Regarding AVF were gaps related to puncture and turnover. It was found that the management nurses presented a higher level of knowledge (p-0,04). Bottom line: The weaknesses and strengths in relation to nurses' knowledge about hemodialysis therapy were identified and, in this way, educational interventions will be guided.